KSR1- and ERK-dependent translational regulation of the epithelial-to-mesenchymal transition - Rao, Chaitra; Frodyma, Danielle E; Southekal, Siddesh; Svoboda, Robert A; Black, Adrian R; Guda, Chittibabu; Mizutani, Tomohiro; Clevers, Hans; Johnson, Keith R; Fisher, Kurt W; Lewis, Robert E (eLife, 2021)
The epithelial-to-mesenchymal transition (EMT) is considered a transcriptional process that induces a switch in cells from a polarized state to a migratory phenotype. Here, we show that KSR1 and ERK promote EMT-like phenotype through the preferential translation of Epithelial-Stromal Interaction 1 (EPSTI1), which is required to induce the switch from E- to N-cadherin and coordinate migratory and invasive behavior. EPSTI1 is overexpressed in human colorectal cancer (CRC) cells. Disruption of KSR1 or EPSTI1 significantly impairs cell migration and invasion in vitro, and reverses EMT-like phenotype, in part, by decreasing the expression of N-cadherin and the transcriptional repressors of E-cadherin expression, ZEB1 and Slug. In CRC cells lacking KSR1, ectopic EPSTI1 expression restored the E- to N-cadherin switch, migration, invasion, and anchorage-independent growth. KSR1-dependent induction of EMT-like phenotype via selective translation of mRNAs reveals its underappreciated role in remodeling the translational landscape of CRC cells to promote their migratory and invasive behavior.
Keywords: Human; colon cancer cells; human organoids